Depression in adolescents associated with family migration, dysfunctional family and bullying in Huánuco 2018 - Calero, Clariza (2019)
Objectives: Determine if family migration, dysfunctional family and bullying are associated with teenagers depression inside the I.E. Pedro Sánchez Gavidia of Huánuco. Materials and methods: transverse correlation study since it tries to evaluate the relationship between the variables at the same period of time. The population was 400 teenagers, we selected a non-probabilistic random sampling by social stratum with a 95%(α <0.05) reliable level, absolute precision of 5%. Results: of those 165 teenager students, 16.4% present depressive symptomatology, 54.5% were female, the average of age was 14.53 years old. In addition, 26.1% came from other regions, 47.9% had suffered some type of bullying, 21.8% had family dysfunctionality and 39.40% had low self-esteem. Bullying (95% CI, p = 0.003) and self-esteem (95% CI, p = 0.00) presented a significant relationship with depression. Conclusions: An important percentage of depression was determined in teenager which were higher to females. Likewise, a significant relationship was obtained between depression - bullying and depression - self - esteem (intervening variable); no association was found with family migration or family dysfunction.